Evidence that Rieger syndrome maps to 4q25 or 4q27. - Vaux, C (1992)
We report a baby with the features of Rieger syndrome and a de novo interstitial deletion of 4q which includes band 4q26 and an adjoining GTL light band, either q25 or q27. Rieger syndrome is provisionally mapped to 4q23----q27 but band 4q26 has been excluded as a possible site, suggesting that Rieger syndrome must map to a band, either 4q25 or 4q27, adjoining 4q26.